Uneven Marriages and the Disintegration of Socioeconomic Boundaries in the Spanish Theater at the End of the 18th Century - Ruiz Hernández, Óscar (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
In this article I examine six Spanish plays belonging to the “popular” trend that debate the social, economic, and racial movements that occurred through marriages between different social classes, ethnic groups, or cultures in the last third of the 18th Century. Among the works collated, my analysis focuses, for the first time and with detail, on Ramón de la Cruz’s sainete El casamiento desigual (1769). Furthermore, I use in an innovative way the theoretical concepts of cross-border social migration and the reconfiguration of one’s identity through their social limits, to explain the alterity and behavior of these dramatic characters who are placed in an eccentric liminal space and not recognized by the Spanish society of the late Eighteenth Century. The analysis of these works allows me to show the feelings of Spanish ordinary people, who were against accepting these social and ethnic changes, as well as the attempts of the incipient middle class to thrive in the social hierarchy. These conflicts manifest the beginning of the collapse of the Old Regime’s feudal system at the end of the 18th Century.